"Sport knowledge creates value" Old age on the move: physical activity to promote physical and cognitive health in old age - Claudia Voelcker-Rehage (Bern Open Publishing, 2023)
Against the background of demographic change, health in old age is an important topic. This applies not solely to healthy older adults living independently but also to residents of nursing homes. Physical activity and exercise are essential determinants of maintaining health throughout the entire life span. In this regard, physical activity and exercise are central to physical as well as cognitive health. However, not all exercise programs are universally effective. There are differential effects on different bodily systems and interindividual differences in responses to physical activity or exercise. Therefore, tailored exercise programs that meet the individual needs of older adults are increasingly in focus. This talk will review research on physical activity in older adults concerning various dependent variables, such as physical fitness, motor function, cognition, and dual-tasking. Additionally, findings for different target groups will be presented, from healthy older adults to the very old and multimorbid in long-term care settings. The aim is to highlight how physical activity and exercise can contribute to physical and cognitive health in old age. Particular emphasis will be placed on individualization and studies conducted in scenarios close to everyday life.